RELIGIOUS AND SECULAR HUMAN DEVELOPMENT COMPARATIVE STUDY APPROACHES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Man Since when did he feel that he was a special, ghostly being in the heart of nature, what does the history of myths and legends indicate about his mental and imaginary imaginations. Did these imaginations of a person give correct information about himself and the world, or were they all just the fruit of ideals and delusions? Where is the truth? Since when did a person begin to understand the truths about himself and the world, when does the period of formation of his fixed belief begin?These questions are not new for the reader, of course, many scientists have been puzzling over these questions for a long time. But every researcher has his own view and conclusions. According to Ramiz Aminov, the spiritual history of mankind consists of long researches, teachings, worldly knowledge, and the history of religions. As a person develops intellectually, culturally, and from the point of view of faith and belief, step by step, step by step, even though new cultures, discoveries, and religious beliefs end up denying the previous ones, but in fact, hereditary continuity is legal here. ruled. World religions, especially monotheistic religions based on the idea of tawhait, have had an incomparable importance for the development of mankind.